Markets for information: of inefficient firewalls and efficient monopolies - Antonio Cabrales; Piero Gottardi (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper we build a formal model to study market environments where information is costly to acquire and is of use also to potential competitors. In such situations a market for information may form, where reports - of unverifiable quality - over the information acquired are sold. A complete characterization of the equilibria of the game is provided. We find that information is acquired when its costs are not too high and in that case it is also sold, though reports are typically noisy. Also, the market for information tends to be a monopoly, and there is typically inefficiency given by underinvestment in information acquisition. Regulatory interventions in the form of firewalls, limiting the access to the sale of information to third parties, uninterested in trading the underlying object, only make the inefficiency worse. On the other hand, efficiency can be attained with a monopolist selling differentiated information, provided entry is blocked. The above findings hold when information has a prevalent horizontal differentiation component. When that is not the case, and the vertical differentiation element is more important, firewalls can in fact be beneficial.
Keywords: D80; 330; Information acquisition; cheap talk; sale of information; Informationsmarkt; Asymmetrische Information; Informationsverhalten; Informationsverbreitung; Potenzieller Wettbewerb; Allokationseffizienz; Internes Kontrollsystem; Monopol; Finanzanalysten; Theorie